Low income housing provision in Malaysia : the role of state and market - Shuid, Syafiee (2008)
The debates on the role of state and market in housing provision in East Asia countries are still consider new. There is still huge gap in the literatures particularly in the low income housing segment. Therefore, the paper aims to examine the role of state and market in housing provision in Malaysia especially for the low income housing. Based on the study in many East Asian countries, there are tendencies for the state to move towards market-oriented in the housing provision. Situation in Malaysia is rather different since the state still actively involved in housing provision and allocation of low income housing. The paper will provide justifications of state continue involvement in the low income housing provision in Malaysia.